Increased urinary 6-hydroxymelatoninsulfate levels in attention deficit hyperactivity disorder diagnosed children and adolescent. (23rd March 2016) - Büber, Ahmet; Çakaloz, Burcu; Işıldar, Yetiş; Ünlü, Gülşen; Bostancı, Hayrani Eren; Aybek, Hülya; Herken, Hasan
Highlights: 1-Daytime, night-time and 24 h 6-OH MS levels were found to be significantly higher in the ADHD group than the control group. 2-There was a statistically significant difference between the ADHD and control groups after adjustment for age and sex. 3-Melatonin production is found to be increased in ADHD. Abstract: There are some studies in attention deficit hyperactivity disorder (ADHD) which note altered circadian rhythms, suggesting abnormalities in melatonin physiology. In order to better characterize the possible melatonin alteration in ADHD, in this study we aimed to detect daytime, nighttime and 24 h levels of 6-hydroxymelatoninsulfate (6-OH MS) in the patients diagnosed with ADHD. Twenty-seven patients between 6 and 16 years-old, who had been diagnosed initially with ADHD, but without other physical and psychiatric disease history and who had not taken psychotropic pharmacotherapy for six months, plus 28 healthy volunteer controls, were included in the study. Urine samples were collected during the whole 24 h cycle, daytime and nighttime separately to assess the time-dependent excretion of the 6-OH MS, which is the main urine metabolite of melatonin. The Enzyme-Linked Immunosorbent Assay (ELISA) method was used for measuring the urine 6-OH MS level. Daytime (15.4 (8.9–24.8) ng/ml vs 6.9 (2.5–15.9) ng/ml, p = 0.002), nighttime (102.9 (65.3–197.7) ng/ml vs 61.5 (37.2–114.4) ng/ml, p = 0.012) and 24 h (54.1 (34.6–83.9) ng/ml vs 27.3 (14.3–48.9) ng/ml, p = 0.000) 6-OH MS levels median (25p–75p) were found to be significantly higher in the ADHD group. After adjustment for age and sex, there was a statistically significant difference between the ADHD group (59.8 ± 4.9) and control group (33.8 ± 4.8) in 24-h 6-OH MS levels (F(1, 51) = 13.673, p = .001, partial η2 = .211). There was no relationship between 6-OH MS levels and Conners Parent Rating Scale short form subscale scores for the ADHD group. These findings indicate that melatonin production is increased in ADHD cases. Further research is needed to determine and thereby understand the mechanisms underlying the higher melatonin production, to assess the impact of altered melatonin on the pathophysiology of ADHD.